PENDEKATAN ANDRAGOGI DALAM PENDIDIKAN ISLAM BAGI PESERTA DIDIK DEWASA - Mawaddah Mawaddah (Lembaga Sepercenter, 2025)
Islamic education is not only intended for children and adolescents, but also plays a strategic role in the development of adult learners. Adult learners have different characteristics, needs, and learning experiences than children. Therefore, conventional pedagogical approaches are often ineffective when applied to adult education. This study aims to examine the concept of andragogy and its relevance in Islamic education for adult learners. The method used is a literature study by analysing various literature related to andragogy and Islamic education. The results of the study show that the andragogy approach is in line with the values of Islamic education because it emphasises independent learning, the utilisation of life experiences, and a contextual and applicative learning orientation. This approach is expected to improve the effectiveness and quality of Islamic education for adult learners.